Bibliometric and visual analysis of cerebral revascularization from 1999 to 2022 - Zhang, Ding; Li, Xiaoqian; Jia, Ni; Chen, Wei; Hu, Yueqiang (Frontiers in Neuroscience, 2023)
Background：Cerebral revascularization is a neurosurgical procedure used to restore the cerebral collateral circulation channel. This study examines the countries, institutions, authors, journals, keywords, and references related to the disease in the field of Cerebral Revascularization from 1999 to 2022 from a bibliometrics perspective, evaluates the changes of knowledge structure clustering, and identifies the new hot spots and new research directions in this field.